Vieillir, dit-elle: Nancy Huston's Feminist Trajectory and Writing Female Ageing. Issue 3 (December 2018) - Averis, Kate
Abstract : This article examines Nancy Huston's writing of female ageing in light of her intellectual and personal trajectory as a feminist thinker. It identifies women's ageing as an integrative and ubiquitous phenomenon in Huston's œuvre, tracing the presence of this thematic and theoretical concern to her very first published works, and outlining its development until her most recent works, before examining a key instance of her fictional treatment of female ageing in Lignes de faille. Drawing on a literary, philosophical and sociological theoretical framework, it argues that Huston furthers feminist approaches to female senescence by inscribing women's experiences of later life not in terms of existential crisis but rather as part of the continuous process of change and transformation inherent to subjective development. The analysis aims to address pressing questions surrounding the intersections of gender and age that are at the forefront of Huston criticism and feminist studies.